بنەما هونەری و پەروەردەییەکانى چیرۆکى منداڵان لە پرۆگرامى خوێندنى قۆناغى بنەڕەتیدا - حسین, پ.ى. د. هیوا کریم; رضا, ئاڤان عثمان عبدالکریم (Sulaimani Journal for Humanities, 2023)
This research is entitled (the artistic and educational foundations of children's stories in the primary education curricula). It is an attempt to introduce the artistic and educational principles of children's stories in the primary education curricula, where children can be taught through stories. Because literature itself is a major field of education and information, this can be achieved through during the curriculum from pre-primary to the final stage of education, it is clear that childhood is the most beautiful stage in human life and the first stage of human acquaintance, understanding and learning. Therefore, good attention should be paid to children's literature, to satisfy all their senses, ideas, minds and imaginations.